The Speciation of Environmentally Significant Metals from Pulp and Paper Mill Effluent with Selected Inorganic Ligands and their Impact on Water Quality of River Nzoia, Kenya - Amayi , James; Muthoka , Titus M.; Lusweti , Kituyi; Omindo , Charles; Oluchina , Sherry (African Journal of Education,Science and Technology (AJEST), 2014)
The effluents from Webuye paper mill were analysed chemically using Atomic absorption spectroscopy to obtain the stoichiometric concentrations of the major anions and cations. However, this does not indicate how the components are distributed amongst possible species. pH was measured with pH meter previously calibrated with pH buffer, alkalinity was determined by titration using phenolphthalein indicator and 0.010 M HCl, chloride was analyzed by titration using potassium chromate indicator and standardized 0.014 N mercuric (II) nitrate solution. A pH dependent model for the speciation of divalent Pb and Cu ions downstream was constructed with corrected IUPAC stability constants using SPECIES computer program. Modelling results showed that inorganic speciation behaviour was of three types; (a) Pb and Cu were dominated by carbonato- complexes at pH 8.0, PbCO3(aq) having 66.06% and CuCO3(aq) 90.45% abundance. Bicarbonato complexes could only form to significant levels at high [HCO3-]T and high ionic strength. (b) Chloro-complexes of Pb and Cu that formed were PbCl+, PbCl2(aq), PbCl22-, CuCl+ and CuCl2(aq). All these complexes were weak and could best be studied in media of high [Cl-]T, high [Cl-]T : [Metal]T ratios and high ionic strength. The fraction of free aquo ions (Pb2+ and Cu2+) dominated speciation with increase in [Cl-] and pH. (c) Hydroxo- complexes of Pb were dominated by carbonato- complexes over a wide range of solution conditions.